Results of a Hepatitis C Virus Screening Program of the 1945-1965 Birth Cohort in a Large Emergency Department in New Jersey. (4th October 2017) - Cornett, Julia Kang; Bodiwala, Vimal; Razuk, Victor; Shukla, Devangi; Narayanan, Navaneeth
Abstract: Background: Persons born between 1945 and 1965 account for an estimated 81% of those infected with hepatitis C virus (HCV) in the United States. However, up to 60% remain undiagnosed. Targeted screening of high-risk populations is essential for reducing HCV-related morbidity and mortality. Prior studies have reported results of HCV screening in large urban emergency departments (ED) with findings which may not be generalizable to other ED settings. Methods: This is a retrospective electronic medical record review of patients in the 1945-1965 birth cohort screened for HCV in a large ED in New Jersey from June 1, 2016 through December 31, 2016. Starting on June 1, 2016, opt-out HCV testing occurred for any patient from this birth cohort seen in the ED from 11AM-7PM as a result of a service grant. The purpose of this study was to determine the prevalence of HCV antibody (Ab) seropositivity and chronic HCV infection in this population as well as analyze specific characteristics of this population, such as birth decade, gender, race/ethnicity and insurance status. Descriptive statistics were performed and using a multivariate logistic regression model, adjusted odds ratios and 95% confidence intervals were calculated. Results: A total number of 3, 046 patients were screened. 55.8% were white, 17.9% were black. 52.1% had private insurance, 33.4% Medicare, and 3.9% Medicaid. 192 were antibody positive (6.3%). Out of these, 109 were white (6.4% prevalence among entire screened population), 47 were black (8.6% prevalence). Ninety-one (5.7%) had private insurance, 73 (7.2%) had Medicare, 14 (11.6%) had Medicaid. 167 had a HCV viral load result. Of the total population, 2.4% had a positive viral load (71/3021). Of those who were HCV Ab positive, 43% had a positive viral load. On multivariate analysis, black race (adjusted OR 3.09, 95% CI 1.82-5.27) and Medicaid (adjusted OR 2.68, 95% CI 1.14-6.28) were independently associated with a positive HCV viral load. Conclusion: Our population had lower rates of HCV Ab seropositivity and chronic HCV infection than reported in prior publications on ED screening of the 1945-1965 birth cohort. Chronic HCV infection was disproportionately associated with black race and Medicaid status. These findings reflect varying prevalence of HCV Ab and positive viral load within this high-risk birth cohort. Disclosures: J. K. Cornett, Gilead Sciences: Service Grant recipient, Grant recipient